Persepsi Dokter, Manajemen, Perawat dan Pasien Terhadap Pemasangan Stent Jantung (Journal of Hospital Management, 2019)
Background. An analysis of the revenue and expenditure carried out by elements involved in the implementation of measures such as doctors, management, nurses and patients is essential dilakukan.karena closely related to the sustainability of the hospital. Cardiac catheterization as a primary modality of treatment of coronary heart disease is very dense high technology with huge costs but will also be featured in the improvement of hospital services revenue. Values have been known to affect the perception of customer satisfaction. This study will examine the perceptions of physicians, management, nurses and patients to cardiac catheterization action in the form of stent gradually. This study will provide an overview and to assess how the cost benefit of the process of action stent gradually in terms of four components involved in the implementation so that the hospital can take decisions or policies relating to the election act gradually or action once the stent on the implementation of patients with coronary heart disease.. Descriptive and comparative analysis between the perceptions of physicians, management, nurses and patients against indicators of questions given to responden.The results descriptive analysis is expected to explain the perception of respondents, the next test average difference with manwithney test to see whether there are differences in the perception of all four components to the actions of cardiac catheterization in the review of the costs and benefits. Perception data in the form of primary data obtained through usage survey to solicit opinions and attitudes opinion of respondents to the implementation of measures of cardiac catheterization and stent. There are very significant differences between the perceptions of the benefits and cost by Mann Whitney test results. Show that in general 50 respondents composed of physicians, management, nurses and patients perceive that the action gradually more profitable in terms of both product benefits, service benefits, personnel benefits and image benefits from the perception of loss of money, time, energy and psychological. Contradicted by the findings of data that patients who continued follow-up only around 10% Keyword: Produck benefit, service benenfit, personnel benefits, image monetary benefit cost, time cost, energy cost, psychological cost.